MENINGKATKAN KECERDASAN KINESTETIK ANAK USIA 5-6 TAHUN MELALUI PEMBELAJARAN TARI KREASI DI PAUD AL-JIHAD - Mujahidatul Mukarromah (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2017)
Kinesthetic inetellingence related to sensitivy and skill to control the coordination of body movement trough rude motoric and soft motoric movement. Kinesthetic intelligence in PAUD Al-Jihad still low especially in terms of balance. One of learning that can improving kinesthetic intelligence is creation dance because creation dance learning is activity that related to body movement. So, this creation learning expected can improve children’s kinesthetic intelligence. This research implemented in Paud Al-Jihad at puskemas street Merak, Cilegon.method that used in this research is Action Reasearch Class (ARC) with two cycle. First cycle consist of 8 meeting and second cycle consist 4 meeting with 75% success criteria. Subject of this research is 15 child consist of 7 boys and 8 girls. Data collection technique in this research consist of observation, field note, interview and documentation. Data analysis used data reduction, data presentation and conclusion. Result of this research know that: 1) Preobservation result children’ kinesthetic intelligence at the low level or not developing. 2) After the children get treatment in first cycle, the children’s skill improved until 50% but still developing. 3) In socend cycle, the children’s skill increase until 79%. So, children’s kinesthetic intelligence development in increasing and developing better. In conclusion, that creation dance learning can improved children’s kinesthetic intelligence 5-6 years old in Paud Al-Jihad.